The role of some important metal oxide nanoparticles for wastewater and antibacterial applications: A review - Taiba Naseem (KeAi Communications Co., Ltd., 2021)
Nanotechnology has great potential to improve water purification and decontamination efficiency. Nanomaterials are efficient at removing organic and inorganic pollutants and heavy metals from wastewater and killing microorganisms. The distinctive characteristics of metal oxides make them the most varied class of materials, and they have properties that cover almost all aspects of solid-state physics and material science. Only a few review articles in the literature specifically address metal oxide nanoparticles and their application in the treatment of wastewater. This review article aims to fill this gap and present a thorough review of the various types of metal oxide nanoparticles in contaminating water impurities. Metal oxide nanoparticles have great potential for treating contaminated water due to their unique properties, such as their large surface areas and low concentration. This paper discussed in detail five metal oxide nanoparticles and their applications for antibacterial and wastewater applications.